Permohonan Rekomendasi Ankum dan Upaya Hukum dalam Menegakkan Keadilan yang Berdasarkan Kepentingan Hukum dan Militer - Arief Fahmi Lubis (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
Law enforcement within the TNI is carried out jointly in a military criminal justice system, which involves several elements, including: Investigators, Ankum, Prosecutors and Papera. Papera/unit commanders have the obligation to guide soldiers in determining their careers according to the competencies required by TNI regulations. The desire and hope of a Papera/unit commander is for the subordinates/soldiers under him to do their best for the progress of the TNI organization he leads, but in fact, for some reason, there are some Soldiers who violate the laws and regulations, by committing criminal acts. The aim of this research is to show that superiors who have the right to punish (Ankum)/unit commanders have the obligation to guide soldiers in determining their careers according to the competencies required by regulations within the TNI. The desire and hope of a unit commander is for the subordinates/soldiers under him to do their best for the progress of the TNI organization he leads, but in fact, for some reason, there are some Soldiers who violate the laws and regulations, by committing criminal acts. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that in the ongoing legal process, superiors who have the right to punish (Ankum) and Papera have 2 (two) paths in an effort to defend their service members from being punished or dishonorably dismissed (fired) due to considerations of military interests. with several considerations such as the TNI soldier having abilities that are really needed by the unit, the TNI soldier being assessed for good behavior on a daily basis or other considerations, so that Ankum can try through these 2 (two) paths, namely providing recommendations to be retained as a TNI soldier and submitting efforts law according to statutory regulations.